Evaluation of Psychometric Properties of the Second Version of the Taqwa (Piety) Questionnaire in Bahasa Melayu - Seghatoleslam, Tahereh; Habil, Hussain; Sulaiman, Ahmad Hatim; Ardakani, Abolfazl; Ishak, Khafidz; Abd Rashid, Rusdi (Springer, 2018)
The aim of the study is to evaluate the psychometric properties of the Bahasa Melayu version of the Taqwa (piety) questionnaire, used for the measurement of behaviour of Drug Dependency Syndrome (DDS), in Malay patients. A sample of 98 males with a psychiatric diagnosis (DSM-IV-R) as the DDS was randomly selected from Kajang Khafidz Polyclinic Kuala Lumpur, Malaysia. After receiving their agreement to attend the study, they completed the Taqwa (piety) questionnaire. The reliability was assessed by determining the Cronbach’s α to measure the consistency of related questions for all four dimensions (subscales), including individual, social, cognitional, and emotional Taqwa behaviour. In the next step to evaluate the composite reliability, convergent, and discrimination validity, a measurement model was determined via Conformity Factor Analysis (CFA) based on Partial List Square method (Smart- PLS Ver: 2M3). The reliability of four dimensions of the questionnaire was acceptable (α1=0.881,α2-0.862,α3=0.86,andα4=0.90)and correlated to each other. However, according to the CFA method, the items with low loading factor (<0.5) were excluded from each dimension. Item 24 and 35 that were related to individual Taqwa, and item 35 that belonged to emotional Taqwa were excluded from the analysis. The composite reliability and convergent, and discrimination validity were satisfied in all conformity factor loading that exceeded 0/05. The psychometric properties of the Taqwa questionnaire are acceptable, and the scale is a good instrument for assessing the Islamic attitude, beliefs, and behaviour of the Bahasa Melayu DDS patients.